Assessing the impact of psychological processes on leader alliance performance expectations and alliance structuring. (2015) - Luvison, Dave; Cummings, Jeffrey L.
There is increasing evidence that leaders make decisions on the basis of subjective frameworks, suggesting that psychological processes play an important role in the manner in which performance expectations and the structure firms employ to meet those expectations are determined. However, despite calls for greater investigation into these processes, there has been little investigation into the psychological factors that influence the way leaders form and operate their firms' strategic alliances. Utilising both upper echelons and goal orientation theories we discuss the manner in which leaders' goal orientation can influence their performance expectations and cause them to structure governance models, develop their firm's alliance capability and encourage the development of organisational cultures conducive to alliance success. This perspective offers a new way to understand the ex ante evaluation processes used to create alliances, leading to a number of implications for future research.